Synthesis, crystal structures and characterization of four coordination polymers based on 5-amino-2,4,6-triiodoisophthalic acid - Zhang, Kou-Lin; Chang, Yan; Zhang, Jing-Bo; Yuan, Li-Min; Deng, Ye; Diao, Guo-Wang; Ng, Seik Weng (Elsevier, 2011)
One homochiral 1D coordination polymer [Cu(ATIBDC)(2,2′-bipy)] ·3H2O·CH3OH (1) and three achiral 1D coordination polymers: [Cd(ATIBDC)(2,2′-bipy)(H2O)] ·3H2O (2), [Cd(ATIBDC)(phen)(H2O)]·4H 2O (3), and [Mn(ATIBDC)(phen)2]·5H2O (4) have been synthesized and characterized (H2ATIBDC=5-amino-2,4,6- triiodoisophthalic acid, 2,2′-bipy=2,2′-bipyridine, and phen=1,10-phenanthroline). Extended high dimensional network architectures are further constructed with the help of weak secondary interactions, such as hydrogen bonding, aromatic stacking, and halogen bonding (CI...π and CI...N/O). Complex 1 crystallizes in the monoclinic system with chiral space group P2(1) and exhibits a right-handed 21 helical chain structure. The homochirality of 1 was confirmed by CD spectrum. Interestingly, two new configurations of decameric water cluster are found in 3 and 4. The acyclic tetrameric cluster (H2O)3(CH3OH) in 1 and (H2O)4 in 2 array into highly ordered helical infinite chains. Thermal stabilities of all the complexes have been studied. Solid state fluorescent properties of the Cd(II) complexes have been explored. © 2011 Elsevier Inc. All rights reserved.